Implementation of Modern Learning Theory of John Dewey’s Teaching Methods and Information Processing Theory in SD Negeri 1 Pesangkalan - Isa Bowo Yunianto (Proceedings Series on Social Sciences & Humanities, 2025)
This study discusses the application of John Dewey's teaching methods and information processing theory in the context of education in SD Negeri 1 Pesangkalan. John Dewey emphasized the importance of experience in the learning process, where students gain understanding through direct involvement in learning activities. Meanwhile, information processing theory describes how students receive, process, and store information to improve learning effectiveness. This paper also examines the implementation of this method in the Independent Curriculum at SD Negeri 1 Pesangkalan, especially in project-based activities (P5) that involve experiential learning, such as robusta coffee processing. The results show that this approach increases students' enthusiasm and understanding of the teaching material.